Thailand : Northeast Economic Development Report - World Bank (Washington, DC, 2012)
This report is about balanced economic development in the Northeast of Thailand. It is about growth and poverty reduction, cities and villages, enterprises and workers, skills and education, infrastructure and trade, and rice and silk. Northeast economic development is only part of Thailand's development challenge, but it is among the most important. We look back at how the Northeast has fared in terms of growth, poverty reduction and social capital over the last decades relative to other regions in Thailand. The report examines today's challenges, analyzes the constraints facing those who seek to meet these challenges, and then proposes an agenda that both outlines a general strategy and the specific priority actions.